Studying the effect of the geometric section shape of bourdon tube on the of tube tip (Latakia University Journal -Basic Sciences Series, 2020)
Bourdon type pressure devices are used to detect pressure in industrial installations and pressure monitoring systems. Bourdon tubes are manufactured in various engineering shapes, circular-C, helical and spiral, to serve the use of this tube in terms of positioning and accuracy. C-Bourdon tube is designed by turning round tubular element to form part of circle. To obtain high product quality at maximum yield, we need an accurate measurement of pressure values ​​in multiple installations. The end of the Borden tube is a pressure-sensitive element. The applied input pressure causes the tube end to be shifted or deviated from the initial position. In this study, the pressure measurement in Borden tube was simulated at different sections and with different axial ratios of Ni-Span metal to obtain the best tube end deviation using the solidworks program. Digital results expressing the deviation of the tube end were obtained when applying pressure and it was observed that the regular sections had better effectiveness and response than the irregular sections.